Adverse Skin Reaction to Hand Hygiene and Personal Protective Equipment among Health-Care Workers during COVID-19 Pandemic in Dr. Mohammad Hoesin General Hospital Palembang - Nopriyati Nopriyati; Deddy Deddy; Muhammad Athuf Thaha; Sarah Diba; Suroso Adi Nugroho; Mutia Devi (HM Publisher, 2022)
Background: Indonesian health-care workers (HCWs) are at the front liners battling against the Coronavirus-2019 disease (COVID-19) pandemic since March 2020 and must protect themselves by hand hygiene and using personal protective equipment (PPE). Hand hygiene and the use of PPE are associated with an adverse skin reactions. This study aimed to find out the prevalence, characteristics, and risk factors for adverse skin reactions to hand hygiene and PPE among HCWs in Indonesia during the COVID-19 pandemic. Methods: A cross-sectional online questionnaire-based survey among HCWs in Dr. Mohammad Hoesin General Hospital Palembang on April 1-30, 2022. The data were collected, including demographic characteristics, occupational-related characteristics, and adverse skin reactions. Results: The study included 134 respondents, the majority of the respondents were female (57,5%), with a mean age was 31,18 ± 4,89 years old. Adverse skin reactions were reported only on 16,4% of respondents. Hands (40,9%) were the most common site affected. The highest symptom and lesion were itch (54,5%), erythema (59,1%) and scales (59,1%). There was a significant association between adverse skin reactions to hand hygiene (p <0,001) and PPE (p = 0,001) before and during the pandemic. However, adverse skin reactions were not associated with increased frequency of hand hygiene and duration of PPE worn. History of pre-existing inflammatory skin condition is the risk factor for adverse skin reactions to hand hygiene and PPE. Conclusion: Adverse skin reactions to hand hygiene and PPE are increasing among Indonesian HCWs during the COVID-19 pandemic.